PERMASALAHAN PESERTA DIDIK KELAS AKSELERASI DI SMP NEGERI 5 PADANG - Handoko, Handoko; Kasih, Fitria; Jarudin, Jarudin (Bimbingan dan Konseling, 2013)
Acceleration means that the speed of learning as the implications of studying complete systems (master learning) also showed learners have extraordinary intelligence and are able to achieve a predetermined competence is much faster and has a very good result, learners who have exceptional intelligence is a characteristic special is not much need time and assistance in completing accelerated predetermined competencies, such as remedial and enrichment programs. The problem in this study is what are the problems of students in accelerated classes SMP Negeri 5 Padang. This study aimed to describe: The problems of students in learning tasks load and peer social relationships particularly accelerated classes at SMP Negeri 5 Padang. This research is a descriptive study sought to describe a situation for what it is. The population in this study were students in accelerated classes SMP Negeri 5 Padang. Sampling in this study using stratified random sampling. So the sample size in this study were as many as 43 people. The instrument used in this study was a questionnaire. As for the use of data analysis techniques percentage. Results of this study reveal that: Problem learners as follows: 1. Load assignments a lesson). Of individuals included in the category of problematic enough, b) From the teachers including the category is less problematic, c) From the family including the less problematic category, 2. Problems of students in a peer social relationships) of individuals including the less problematic category, b) of the learning environment including the less problematic category, c) From playing environment including the less problematic category. The conclusion is: The problem learners accelerated classes at SMP Negeri 5 Padang fall into the category of less problematic. However the researchers looked less problematic category does not mean students get guidance and counseling services which become one of the purposes of this study. Based on the results of these studies recommended a material by providing services such as information services, content services, guidance services and counseling groups to create an atmosphere of classroom learners better acceleration.